An Analysis of the Reinforcement Used by the Teachers at Little Sunshine Learning Center Singaraja in the Academic year 2015/2016 - ., Luh Putu Nia Arnida Putri; ., Prof. Dr. Ni Nyoman Padmadewi,MA; ., Drs.Gede Batan,MA (Jurnal Pendidikan Bahasa Inggris undiksha, 2016)
Penelitian ini bertujuan untuk menganalisis tentang penguatan yang digunakan oleh guru-guru di Little Sunshine Learning Center Singaraja. Focus dari penelitian ini berkaitan dengan jenis-jenis penguatan yang digunakan oleh guru-guru di Little Sunshine Learning Center Singaraja selama proses pembelajaran dan respon siswa setelah diberikannya penguatan oleh guru. Dalam hal ini penulis menganalisis penguatan yang diberikan guru di dalam kelas dengan cara observasi. Hasil dari analisis menunjukkan bahwa guru-guru di Little Sunshine Learning Center Singaraja menggunakan penguatan positif dan penguatan negatif baik penguatan verbal maupun penguatan nonverbal. Respon siswa setelah diberikannya penguatan antara lain siswa semakin berpartisipasi aktif dalam mengikuti pembelajaran serta meningkatkan motivasi dan keantusiasan siswa. Pemberian penguatan negatif juga membuat siswa tau tentang apa yang mereka bisa dilakukan dan yang tidak bisa dilakukan. Kata Kunci : Penguatan, penguatan positif, penguatan negatif This research aimed at analyzing the types of reinforcements used by the teachers at Little Sunshine Learning Center Singaraja. The focus of this research is related with the types of reinforcements used by the teachers at Little Sunshine Learning Center Singaraja during teaching and learning process and the students’ responses after being reinforced by the teacher. This research used descriptive qualitative study. The writer analyzed the reinforcement used by the teacher in the classroom through the observation. The result of the analysis showed that the teacher at Little Sunshine Learning Center Singaraja used positive reinforcement and negative reinforcement both verbal and nonverbal. The students’ responses after being reinforced were they participated more actively in the classroom and also increased the students’ enthusiasm. Negative reinforcements also make the students know what they could do and they could not do. So, it could control their misbehavior too.keyword : Reinforcement, positive reinforcement, negative reinforcement